Forensic examination of grievous hurt: A critical analysis of section 320 of the Malaysian penal code - Masum, Ahmad; Ahmad, Muhamad Hassan; Nafees, Seeni Mohamed (Journals Online, 2021)
Grievous hurt is a hurt of a more serious nature. In Malaysia, the definition of grievous hurt under section 320 of the Penal Code has remained essentially unchanged since its inception. In a criminal trial for the offence of grievous hurt, opinion of an expert of forensic medicine becomes necessary in order to ascertain the nature of the injuries, duration of the injury, weapons etc., which have been probably used to cause the injury. Medical experts are required to mention in their injury report against every injury whether it is simple or grievous in nature. If the nature of the injury cannot be immediately ascertained, then the patient should be kept under observation and entry to this effect should be made in the relevant column of the medico legal report. The paper aims to examine the role of medical experts as well as to minimise the dilemma faced by them in the process of providing their expert opinion. The paper adopts a legal-library based research methodology. The paper concludes that a medical expert who is examining an injured person has to opine that the injury in question is one or the other of the type recognised as grievous‟ under section 320 of the Penal Code. It is the duty of a medical expert to know the law correctly and apply them in their strict sense. It is finally the Judiciary which will interpret the law and apply it according to the facts and circumstances of each case.